2020
DOI: 10.1007/978-3-658-29267-6_8
|View full text |Cite
|
Sign up to set email alerts
|

COPD Classification in CT Images Using a 3D Convolutional Neural Network

Abstract: Chronic obstructive pulmonary disease (COPD) is a lung disease that is not fully reversible and one of the leading causes of morbidity and mortality in the world. Early detection and diagnosis of COPD can increase the survival rate and reduce the risk of COPD progression in patients. Currently, the primary examination tool to diagnose COPD is spirometry. However, computed tomography (CT) is used for detecting symptoms and sub-type classification of COPD. Using different imaging modalities is a difficult and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The identified subset of features is then used for a simple multiple logistic regression for the training data and the model is used to predict the presence of the phenotype for the test data. In addition to these feature‐based approaches, a specifically developed 3D DL algorithm 39 is used to automate the detection of emphysema based on the segmentation of the entire lung (more information can be found in the Section S2). This 3D DL algorithm was pretrained on COPDGene 30 where it achieved an AUC of 81% for COPD detection based on GOLD stage criteria, comparable to the state‐of‐the‐art 2D DL method of Gonzalez et al that achieved 86% 17 …”
Section: Methodsmentioning
confidence: 99%
“…The identified subset of features is then used for a simple multiple logistic regression for the training data and the model is used to predict the presence of the phenotype for the test data. In addition to these feature‐based approaches, a specifically developed 3D DL algorithm 39 is used to automate the detection of emphysema based on the segmentation of the entire lung (more information can be found in the Section S2). This 3D DL algorithm was pretrained on COPDGene 30 where it achieved an AUC of 81% for COPD detection based on GOLD stage criteria, comparable to the state‐of‐the‐art 2D DL method of Gonzalez et al that achieved 86% 17 …”
Section: Methodsmentioning
confidence: 99%
“…Experimental results showed that the recognition method based on CNN is before the method based on SVM. MFCC features are utilized to identify the lung sounds by a 5-Layer CNN (5L-CNN), and better recognition results are obtained in [1]. They used a variant of 3D VoxResNet for COPD emphysema classification.…”
Section: Related Workmentioning
confidence: 99%
“…5 Spectrogram of input after denoising spectrum line energy of the lung sounds is filtered by using a Mel filter bank. The function of filters is expressed using (1).…”
Section: Input Processing Of the Lung Sound Datamentioning
confidence: 99%
“…These models evaluate the local intensity distribution or use texture-based information to discern emphysema in CT [19,20]. Deep learning models, such as 3D convolutional neural networks (CNNs), deep-CNNs with long short-term memory and transfer learning models like 3D ResNet have been found to detect emphysema with acceptable performance [21,22,23]. However, all these approaches primarily make use of HRCT and there is a dearth of studies on low-dose CT for automatic detection of emphysema.…”
Section: Related Workmentioning
confidence: 99%